MOLEKULYAR FIZIKA BO‘LIMI MAVZULARINI O‘QITISHDA YANGICHA METODIK YONDASHUV - Karimova, O.A. (SCIENCE and SOCIETY, 2023)
This article describes the new methodological foundations for the development of students' logical thinking skills using modern educational technologies.
Keywords: innovation; technology; learning; heat; engine; cube; thinking; temperature; heater; cooler; method; energy